MANAGEMENT OF QUALITY LEARNING IN A SUPERIOR CLASS - Suresmi Suresmi; Yurnalis Etek; Agus Pahrudin; Ahmad Fauzan; Siti Patimah (Edukasi Islami: Jurnal Pendidikan Islam, 2020)
The existence of a superior class in madrasah is an institution that is specifically designed and developed systematically, adequate facilities / infrastructure, curriculum, qualified teaching and education staff, and others. The existence of a superior class can increase the competitiveness of madrasas and the bargaining rank of madrasas as superior madrasas will be even stronger. To increase the competitiveness of these madrasas as superior madrasas, it is necessary to properly manage quality learning. The article discusses planning, organizing, implementing quality learning in superior classes at MTsN 2 Bandar Lampung and at MTsN 2 Tanggamus. This research is a field research, using a qualitative approach with a multisite study design. The data technique used interview, observation and documentation techniques. descriptive data analysis techniques with Interactive Model Analysis. The results of the study, planning learning in superior classes at MTsN 2 Bandar Lampung and MTsN 2 Tanggamus through standard design after midle input, excellent academic process standards based on spiritual learning, and superior output standards. The design standards referred to are enriched curriculum design standards (enriched curriculum), appropriate educational staff, IT media, classroom arrangement, and time allocation designs. Organizing learning in the superior classes of MTsN 2 Bandar Lampung and MTsN 2 Tanggamus through organizing an enriched curriculum (enriching the curriculum) with the Olympic curriculum, language and religion, organizing the allocation of learning time, organizing the roles and assignments of teachers, and organizing learning resources.